A cohort analysis of labor participation in Mexico, 1987 - 2009 - Robert Duval-Hernández; Pedro Orraca Romano (Institute for the Study of Labor (IZA), 2009)
This paper conducts a cohort analysis of labor participation in urban Mexico in recent decades. The rates analyzed are the labor force participation, the unemployment rate, and the employment shares of the formal and informal salaried sectors, as well as of self-employment. These rates are decomposed into age, cohort, and time effects. The life cycle patterns of labor force participation and formal employment follow a standard inverted U-shape. Younger workers are more likely to participate in the informal salaried sector, while self-employment increases monotonically with age. However, significant informal salaried employment is also observed among older unskilled workers and women of different ages. Strong countercyclical variations are observed for the informal salaried sector, while the opposite occurs for the formal sector. Self-employment fluctuations are for the most part acyclical. These facts support a mixed view of the labor markets whereby some informal sector workers are rationed out of the formal sector, while others go into this sector voluntarily. The analysis also indicates that the female labor force is countercyclical, suggesting the existence of an added worker effect. Long-run generational effects show a steadily rising participation in the informal sector with a corresponding decline in formality among newer generations of salaried workers. Some preliminary explanations for this fact are discussed.
urn:nbn:de:101:1-2009100257
Keywords: J21; O17; O54; 330; Labor force composition; informal sector; Latin America; Arbeitsangebot; Kohortenanalyse; Mexiko